Black, LGBT and from the Favelas: an Ethnographic Account on Disidentificatory Performances of an Activist Group in Brazil - Mascarenhas Neto, Rubens; Zanoli, Vinícius (Culture Unbound, 2019)
In this article, we address the processes of the production of places, identities, and cultures through analysing performances of activists from Aos Brados, in their political activities throughout Campinas, a 1 million inhabitants city located in the state of São Paulo, Brazil. Aos Brados is an activist group formed by Black LGBT people from the favelas whose main activities in the last ten years have been cultural activities. Focusing on the activities made by Aos Brados members in cultural centres and public spaces throughout Campinas, we discuss how, in such presentations, the group disputes meanings associated with the places and cultures that these places claim to represent. We sustain that it can be seen as a process of disidentification in which Aos Brados reshapes meanings associated with places and cultures, producing Black LGBT Culture from the favelas. The discussion results from shared questions in two different research concerning the effects of the intersections of race, gender, class, and sexuality on the political identity of Black LGBT activists and on the performances of young drag queens. The methodology employed congregated participant-observation and in-depth interviews.